A Study on the Effects of Firefighters’ Job Autonomy and Job Satisfaction on Organizational Commitment - Choi, Bok-Mu; Kong , Ha-Sung (International Journal of Membrane Science and Technology, 2023)
This study empirically analyzed the effects of job autonomy and job satisfaction on organizational commitment of firefighters performing the current standard daily routine for firefighters, and aimed to provide basic data for standard days and improvements that reflect the working environment and dispatch characteristics. It is unreasonable to uniformly apply the current standard routine to the unpredictable dispatch environment of firefighters. As a result of analyzing a sample of firefighters nationwide, it was found that the current standard work and performance hindered job autonomy and job satisfaction. As a result of empirical analysis with job autonomy and job satisfaction as independent variables and organizational commitment as a dependent variable, it had a positive (+) effect. Therefore, the results of this study suggest that there is a need to increase organizational commitment through the current standard work and improvement of firefighters. However, there is a limitation in that research does not reflect all matters such as differences in work patterns by region, characteristics of dispatch by region, and characteristics by position, and it should be improved into a standard routine that can be commonly applied to firefighters nationwide through future research.